(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The rapid development of globalization and digital technologies has significantly transformed the field of English language education. Traditional teacher-centered approaches are gradually being replaced by learner-centered methodologies that encourage communication, collaboration, and critical thinking. This article explores the role of innovative teaching methods in improving English language proficiency and enhancing students’ motivation. It also discusses the integration of technology, project-based learning, and interactive activities in language classrooms. The findings suggest that innovative methodologies create a more engaging learning environment and contribute to the development of communicative competence.